Prevalencia y factores asociados a dermatosis en la población adulta de Honduras, 2017-2018 - Katia Aguilar Gutiérrez; Aleydi Gómez Campos; Kathya Chinchilla Castañeda; Edna Maradiaga; Manuel Sierra; Mauricio Gonzales; Xenia Velásquez (Revista Médica Hondureña)
Introduction: In dermatology, there are more than 2,000 entities, some of which affect an individual of any age group at a given moment without distinction of race or sex. The last report in The Global Burden of Disease (2014) revealed that the prevalence of dermatoses in general ranged between 30% and 70%. Objec-tive:Determine the prevalence and factors associated with der-matoses in adults ≥ 18 years in areas of influence of the Medical Doctors in Social Service of the National Autonomous University of Honduras (UNAH), November 2017–November 2018. Methods:Transversal descriptive study with association analysis, carried out in the 18 departments of Honduras, included the adult popula-tion ≥ 18 years old in the geographical areas of influence of 254 Doctors in Social Service. The sampling was multistage random, assigning each one 50 ± 2 adults over 18 years of age, total sample of 12,775 adults. An interview was applied, performing univariate and bivariate analysis, prevalence ratio and 95% CI, with values of p<0.05. Results:A prevalence of dermatoses of 43.4% was found. Among the associated factors: female sex (PR=1.03, CI= 95% 1.01-1.06, P=0.00026), comorbidities (PR=1.53, CI=1.46-1.61, P=0.00000), hours of sun exposure 9am to 4pm (PR=1.07, CI=1.04-1.11, P=0.00000). Discussion:There is an association between the presence of comorbidities and dermatoses, and it is established that solar exposure is a risk factor associated with the presence of dermatoses in the studied population.